Building energy simulation : a workbook using designbuilder - Garg, Vishal; Mathur, Jyotirmay; Bhatia, Aviruch (Boca Raton : CRC Press, 2020)
'The 2nd edition of Building Energy Simulation includes study of various components and systems of a building and their effect on energy consumption, with the help of DesignBuilderTM, a front-end for EnergyPlus simulation engine, supported by examples and exercises. Following a'learning by doing' methodology, it explains simulation input parameters and how to do analysis of the simulation output explaining building physics and energy simulation. Divided into three sections, it covers fundamentals of energy simulation followed by advanced topics in energy simulation and simulation for compliance of building codes and detailed case studies for whole building energy simulation'--
Includes bibliographical references and index.
Keywords: Buildings -- Energy conservation; Buildings -- Mechanical equipment -- Computer simulation